Research about Teachers and with Teachers, and its Impact on Teacher Training. How to Conduct the Research? - Francisco Imbernón Muñoz (Universidad Autónoma de Baja California, 2012)
Education, like all social practice, has an ontological and methodological plurality. It delves into research processes that lead to a different way of seeing education and that both contribute to and seek various aspects such as the accumulation, prediction, description, explanation, comprehension, interpretation, emancipation, deconstruction, organization and progressive creation and reordering of its field of knowledge. The diversity of research about teachers and with teachers, which shows us education as it is today, not only evinces a state of normality in such a complex social field as education, but also reveals a wealth of processes, not stagnation or paralysis.